2017
DOI: 10.18488/journal.2.2017.75.165.175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Concrete Structures Reinforced with Fiber Reinforced Polymers Bars: A Review

Abstract: Article HistoryThe behavior of concrete members reinforced with fiber reinforced polymer (FRP) bars has been the focus of many studies in recent years due to their excellent corrosion resistance, high tensile strength, and good non-magnetization properties. However, the low modulus of elasticity of the FRP materials and their non-yielding characteristics results in large deflection and wide cracks in FRP reinforced concrete members. This review was focusing in different behavior of FRP bars in reinforced concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…We use a PD code implemented to run on a single CPU with an NVIDIA Tesla P100 GPU [23]. The PD simulations using the smallest horizon (and densest grids) over 10k time steps take about 10 minutes to complete on an Intel Xeon E5-2670 2.60-GHz processor with the Tesla P100 GPU.…”
Section: A Brief Review Of Peridynamicsmentioning
confidence: 99%
“…We use a PD code implemented to run on a single CPU with an NVIDIA Tesla P100 GPU [23]. The PD simulations using the smallest horizon (and densest grids) over 10k time steps take about 10 minutes to complete on an Intel Xeon E5-2670 2.60-GHz processor with the Tesla P100 GPU.…”
Section: A Brief Review Of Peridynamicsmentioning
confidence: 99%
“…In the last decade, Important efforts have been made to apply FRP Composite materials to the construction sector and, finally, structural uses of composite materials have started to emerge in civil infrastructure structures. FRP materials used as interior and exterior reinforcements in the field of structural engineering [3]. The high tensile strength, lower density, higher rigidity, chemical resistance, and other properties characterise FRP.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant research activities have shown that FRP materials can be used successfully to reinforce RC structures [5,6]. High-tensile fibre stiffeners including aramid, carbon and glass are mixed into polymer arrays and are manufactured in various forms and characteristics such as rods, grids and tubes [3]. FRP reinforcement also offers an opportunity for fast incorporation of optical fiber strain measuring devices of structural health monitoring applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several structures as instant tunnels may be subject to accidental or man-made explosions during the service time [12][13][14][15][16][17][18][19]. It leads to the fact that the concrete material is in danger of fire exposure and dynamic loads simultaneously.…”
Section: Introductionmentioning
confidence: 99%